EKSISTENSI DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DALAM KETATANEGARAAN INDONESIA - Hardiman Mustakim (JURNAL AKTA YUDISIA, 2026)
The Regional Representative Council (DPD) of the Republic of Indonesia is one of the state institutions resulting from the amendment to the 1945 Constitution which reflects the spirit of reform to create a more democratic and representative state system.  The aim of the research is to find out what the function of the Regional Representative Council is in the Indonesian state system, to find out why the existence of the Regional Representative Council is necessary in parliament. The research used in this study is normative research, research conducted by examining library materials.  The function of the Regional Representative Council of the Republic of Indonesia in the Indonesian state system reflects its strategic role as a regional representative in the government system. Although its authority is limited compared to the House of Representatives, the Regional Representative Council plays a crucial role in maintaining a balance between central and regional interests, as well as in strengthening the democratic and decentralization system in Indonesia. The existence of the Regional Representative Council of the Republic of Indonesia is necessary in the Indonesian parliament because it acts as a regional representative, a counterweight to the House of Representatives, and a protector of regional autonomy interests within the unitary state. Although its authority still needs to be strengthened, the presence of the Regional Representative Council of the Republic of Indonesia is a strategic step in realizing inclusive democracy and equitable development.